Axonal Polyneuropathy in A Child with Respiratory Failure: A Case Report of Plasmapheresis- Associated Recovery - Mai Mohammed Mostafa; Sohaila Ali Abd El-Halim (Pediatric Sciences Journal)
In pediatric intensive care units, polyneuropathy may be masked by primary respiratory failure due to overlapping clinical presentations that are frequently attributed to pulmonary disease rather than an underlying neuromuscular disorder. Early diagnosis remains challenging, and evidence for the use of plasmapheresis in pediatric neuropathy is limited. We report the case of a previously healthy 11-year-old child who presented with acute respiratory failure requiring mechanical ventilation. During ventilatory support, no neuromuscular blocking medications were utilized, and sedation was maintained using a continuous intravenous infusion of midazolam. Despite the resolution of lung pathology, the patient remained ventilator-dependent, with multiple failed extubation attempts over 20 days. Neurological evaluation revealed generalized hypotonia, absent deep tendon reflexes, and electrophysiological findings consistent with axonal polyneuropathy. A diagnosis of polyneuropathy, critical illness polyneuropathy (CIP), was considered. The patient showed significant clinical improvement following treatment with plasmapheresis and subsequent intravenous immunoglobulin (IVIg). Neuromuscular disorders, particularly CIP, should be considered in the differential diagnosis of children presenting with unexplained respiratory failure and prolonged ventilator dependence. Early neurological evaluation, including electrophysiological studies, is essential for timely diagnosis and management, thus improving outcomes. Plasmapheresis may offer a beneficial treatment option in CIP, particularly those who remain ventilator-dependent, and are refractory to extubation.